Expression divergence of BAG gene family in maize under heat stress - Babar Farid; Muhammad Abu Bakar Saddique; Muhammad Hammad Nadeem Tahir; Rao Muhammad Ikram; Zulfiqar Ali; Waseem Akbar (BMC Plant Biology)
Abstract Heat stress poses a significant challenge for maize production, especially during the spring when high temperatures disrupt cellular processes, impeding plant growth and development. The B-cell lymphoma-2 (Bcl-2) associated athanogene (BAG) gene family is known to be relatively conserved across various species. It plays a crucial role as molecular chaperone cofactors that are responsible for programmed cell death and tumorigenesis. Once the plant is under heat stress, the BAG genes act as co-chaperones and modulate the molecular functions of HSP70/HSC70 saving the plant from the damage of high temperature stress. The study was planned to identify and characterize the BAG genes for heat stress responsiveness in maize. Twenty-one (21) BAG genes were identified in the latest maize genome. The evolutionary relationship of Zea mays BAGs (ZmBAGs) with Arabidopsis thaliana, Solanum lycopersicum, Theobroma cacao, Sorghum bicolor, Ananas comosus, Physcomitrium patens, Oryza sativa and Populus trichocarpa were represented by the phylogenetic analysis. Differential expressions of BAG gene family in leaf, endosperm, anther, silk, seed and developing embryo depict their contribution to the growth and development. The in-silico gene expression analysis indicated ZmBAG-8 (Zm00001eb170080), and ZmBAG-11 (Zm00001eb237960) showed higher expression under abiotic stresses (cold, heat and salinity). The RT-qPCR further confirmed the expression of ZmBAG-8 and ZmBAG-11 in plant leaf tissue across the contrasting inbred lines and their F1 hybrid (DR-139, UML-1 and DR-139 × UML-1) when exposed to heat stress. Furthermore, the protein-protein interaction networks of ZmBAG-8 and ZmBAG-11 further elucidated their role in stress tolerance related pathways. This research offers a roadmap to plan functional research and utilize ZmBAG genes to enhance heat tolerance in grasses.